Effect of Acute Levodopa Up-Titration on Blood Pressure in Patients With Early Stage Parkinson’s Disease: Results of a Levodopa Challenge Test - He, Xiaoqin; Mo, Chengjun; Zhang, Yi; Cai, Ying; Yang, Xiaodong; Qian, Yiwei; Xiao, Qin (Frontiers in Aging Neuroscience, 2022)
Objective: Levodopa up-titration is the primary therapeutic strategy as the Parkinson’s disease (PD) progresses. However, the effects of levodopa up-titration on blood pressure (BP) are inconclusive. This study aimed to investigate the effect of acute levodopa up-titration simulated by levodopa challenge test (LCT) on BP in patients with early-stage PD. Methods: We monitored BP in 52 patients with early-stage PD using a standardized standing test. BP was assessed in supine position after 10 minutes of rest and at 1 and 3 minutes after standing up. BP was measured in the “off-state” and the best “on-state” during LCT in the morning at hospital. In another day, “off-state” and the best “on-state” BP was measured before and after anti-PD drug uptake in the morning at home. Demographic and clinical features of the patients were evaluated and analyzed. Results: In the LCT, the prevalence of OH in the “off-state” and the best “on-state” was 11.5% and 13.5%, respectively. Additionally, the OH in the best “on-state” was associated with OH in the “off-state” and monoamine oxidase B inhibitor use. Although 38 (73.1%) patients experienced levodopa-induced hypotension during the LCT, no risk factors were identified. While BP reductions were observed after taking anti-PD drugs at home, no further reduction was seen during acute levodopa up-titration simulated by the LCT. Conclusion: Our results demonstrate that acute levodopa up-titration does not exacerbate BP reduction induced by anti-PD drugs at home. BP monitoring is critical for the management of patients with PD.